2016
DOI: 10.1002/qua.25116
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of the reactivity and electronic structure of the transesterification of triacetin in biodiesel production via a sulfated zirconia heterogeneous catalysis

Abstract: This DFT study examined the interaction of a sulfated zirconia (SZ) slab model system (heterogeneous catalyst) and triacetin (a precursor in biodiesel production) using explicit methanol solvent molecules. Full geometry optimizations of the systems were performed at the B3LYP level of theory. Gibbs free energies provide insight into the spontaneity of the reactions along a three-step reaction mechanism for the transesterification of triacetin. Charge decomposition analysis revealed electronic charge transfer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Triacetin was used as a triglyceride model for the kinetic study of this reaction because it has the same chemical functionality as any triglyceride molecule, sharing the same reactivity principles. The transesterification of triacetin with methyl alcohol occurs in three sequential steps, as depicted in Scheme (Muñiz, Castillo, Robles, & Sansores, ).…”
Section: Resultsmentioning
confidence: 99%
“…Triacetin was used as a triglyceride model for the kinetic study of this reaction because it has the same chemical functionality as any triglyceride molecule, sharing the same reactivity principles. The transesterification of triacetin with methyl alcohol occurs in three sequential steps, as depicted in Scheme (Muñiz, Castillo, Robles, & Sansores, ).…”
Section: Resultsmentioning
confidence: 99%
“…The basic knowledge of methanolysis and its competing reaction of triglyceride hydrolysis at the molecular level are of great importance for the development of biodiesel production. A DFT/B3LYP study of glycerol triacetate or triacetin as a model triglyceride compound was conducted in the presence of a sulfated zirconia catalyst and they were detected by the adsorption of triacetin and an alcohol solvent which caused the exchange H of alcohol with the group of triacetin which then causes the transesterification process to produce the experimentally observed methyl acetate (Muniz et al, 2016;Delesma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the direct use of solid acid catalysts for the biodiesel production has not been widely explored due to its limitation of a slow reaction rate and the lack of fundamental theoretical studies about dealing with the reaction pathway of triacylglycerols on solid acids (Lam et al, ). Notably, the density functional theory (DFT) study examined the interaction of a sulfated zirconia (SZ) slab model system, estimating that the strong acidic catalyst could effectively reduce Gibbs free energies of the transesterification for triacetin in biodiesel production on the SZ surface (Muñiz et al, ). Augusto et al used DFT to analyze the H + ‐catalyzed ethanolysis of butyric acid monoacylglycerol, and found that the intrinsic H bonds played a key role in stabilizing the tetrahedral intermediate with the solvent effects being taken into account (da Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%